Lichen planus-like keratosis: clinical applicability of in vivo reflectance confocal microscopy for an indeterminate cutaneous lesion - Nicole Nagrani; Natalia Jaimes; Margaret Olivero; Harold S Rabinovitz (Mattioli1885, 2018)
Lichen planus-like keratosis (LPLK) is an involuting cutaneous lesion often presenting between the fifth and seventh decades of life. These lesions typically appear abruptly as a solitary macule, papule, or plaque that continuously evolves as it undergoes regression. Clinical and dermoscopic features of LPLK can mimic both benign and malignant lesions, often prompting biopsy for accurate diagnosis. We describe a case of LPLK developing in a patient with a history of multiple skin cancers, including melanoma. Dermoscopy revealed peripheral granules and a central area with pinkish-brown pigmentation and a disorganized pattern with shiny white structures and rosettes. Handheld reflectance confocal microscopy (RCM) showed a typical honeycomb pattern with millia-like cysts and comedo-like openings, and lacked pagetoid and dendritic cells. Based on the benign features seen with RCM, the lesion was followed until complete regression was observed. In conclusion, we describe a case of LPLK with clinically and dermoscopically indeterminate features that was successfully monitored with RCM. We intend to highlight the utility of RCM as a diagnostic aid in equivocal lesions in order to prevent unnecessary excisional procedures.